Zero-order metoprolol pharmacokinetics after therapeutic doses: severe toxicity and cardiogenic shock. (20th October 2016) - Isbister, Geoffrey K.; Ang, Karyn; Gorman, Kieron; Cooper, Joyce; Mostafa, Ahmed; Roberts, Michael S.
Abstract: Objective: Acute beta-blocker overdose can cause severe cardiac dysfunction. Chronic toxicity is rare but potentially severe. We report therapeutic dosing of metoprolol resulting in unusual pharmacokinetics and toxicity, given high-dose insulin therapy for treatment. Case details: A 90-year-old female presented with hypotension, tachycardia and severe cardiac dysfunction after commencing a rapidly increasing metoprolol dose of 250 mg split daily. She was admitted to intensive care and given high-dose insulin therapy (10 U/kg/h), noradrenaline, adrenaline and dobutamine for severe cardiac dysfunction (cardiac index, 0.76 L/min/m 2 ). She developed acute renal failure, ischaemic hepatitis and disseminated intravascular coagulopathy. Inotropes and high-dose insulin were weaned over four days with complete recovery. Metoprolol was quantified with liquid chromatography-tandem mass spectrometry and concentration-time data were analysed using MONOLIX ® vs 4.3 (www.lixoft.com ). Admission metoprolol concentration was 2.39 μg/mL (therapeutic reference range: 0.035–0.5 μg/mL). Data best fitted a one compartmental model with Michaelis–Menten kinetics and zero order elimination at high concentrations. Final parameter estimates were V, 63.4 L, maximum rate [ V m ], 9.57 mg h −1, Michaelis constant [ K m ], 1.97 mg L −1 . Predicted elimination half-life decreased from 20 h over time until there was first order elimination with a half-life 9 h. Conclusion: The time course of cardiac dysfunction was longer than acute overdose but consistent with prolonged zero order elimination of metoprolol, suggesting the patient was a poor CYP2D6 metaboliser. High-dose insulin euglycaemia appeared to be effective in combination with vasoconstrictors/inotropes.